Triphenyltin Chloride Delays Leydig Cell Maturation During Puberty in Rats - Li, Linchao; Xie, Lubin; Ma, Leikai; Chen, Yong; Chen, Xianwu; Ge, Fei; Huang, Tongliang; Chen, Lanlan; Hong, Tingting; Chen, Xiaofang; Zhu, Qiqi; Li, Xingwang; et al. (Frontiers in Pharmacology, 2018)
Triphenyltin chloride (TPT) is present in a wide range of human foods. TPT could disrupt testis function as a potential endocrine disruptor of Leydig cells. However, the effect of TPT on pubertal Leydig cell development is still unclear. The objective of the current study was to explore whether exposure to TPT affected Leydig cell developmental process and to clarify the underlying mechanisms. Male Sprague Dawley rats at 35 days of age were randomly divided into four groups and received normal corn oil (control), 0.5, 1 or 2 mg/kg/day TPT for 18 days. Immature Leydig cells isolated from 35-day-old rat testes were treated with TPT (10 and 100 nM) for 24 h in vitro. In vivo exposure to  0.5 mg/kg TPT lowered serum testosterone levels and lowered Star mRNA. TPT at 2 mg/kg also lowered Lhcgr, Cyp11a1, Hsd3b1, Hsd17b3 as well as pAKT1/AKT1, pAKT2/AKT2, and pERK1/2/ERK1/2 ratios. In vitro exposure to TPT (100 nM) increased ROS production and induced cell apoptosis rate in rat immature Leydig cells. In conclusion, TPT exposure disrupts Leydig cell development possibly via interfering with the phosphorylation of AKT1, AKT2 and ERK1/2 kinases.